Reading Paul with the reformers: reconciling old and new perspectives - Chester, Stephen J. (Wm. B. Eerdmans Publishing Co., 2017)
Intro -- Title Page -- Copyright -- Contents -- Foreword -- Preface -- Abbreviations -- Prologue -- I. Hermeneutics: The SixteenthCentury and the Twenty-First Century -- 1. The Hermeneutics of Reform: Erasmus, Luther, and Contemporary Theological Interpretation of Scripture -- 1.1. An Apparent or Real Quarrel? Erasmus and Luther on Paul and Peter at Antioch -- 1.2. Erasmus and Luther on Scripture and Interpretation -- 1.3. Erasmus, Luther, and the Goals of Contemporary Theological Interpretation -- 1.4. Erasmus, Luther, and the Conflict of Interpretations -- 1.5. Erasmus, Luther, and Reception History -- II. Shared Convictions: The Reformers' New Pauline Exegetical Grammar -- 2. The Medieval Context of the Reformers: Pauline Exegesis and Soteriology -- 2.1. Continuity or Discontinuity? The Reformers and Medieval Pauline Interpretation -- 2.2. Augustine -- 2.3. Medieval Appropriations of Augustine's Pauline Exegetical Grammar -- 2.4. The Impact on Luther and the Reaction of the Council of Trent -- 3. The Human Plight apart from Christ: Sin, the Law, and the Conscience -- 3.1. Sin -- 3.2. The Law -- 3.3. Conscience -- 3.4. Summary -- 4. Salvation in Christ: The Works of the Law, Grace, and Faith -- 4.1. Not by the Works of the Law -- 4.2. Grace -- 4.3. Faith -- 4.4. Summary -- III. Individual Perspectives: Luther, Melanchthon, and Calvin on Righteousness in Christ -- 5. Alien Righteousness in Christ: The Integration of Justification by Faith and Union with Christ in Martin Luther's Pauline Exegesis -- 5.1. Luther's account of Justification in its early Protestant Context -- 5.2. Interpreting Luther Interpreting Paul -- 5.3. The Human Plight: Luther's Apocalyptic Anthropology -- 5.4. Christ Present in Faith: Justification and Union with Christ -- 5.5. Receiving Christ's Righteousness -- 5.6. Living an Alien Life -- 5.7. Faith and Good Works.